STUDENTS’ PERCEPTION ON THE USE OF L1 IN ENGLISH CLASSESBY TEACHERS AND STUDENTS AT SMAN 2 PEKANBARU - Anggi Saputra; Hadriana Hadriana; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is aimed to find out the students’ perception on the use of L1 in English classes by teachers and students at SMAN 2 Pekanbaru in the academic year 2017/2018. This is a survey research. The participants answered questions administered through questionnaire which consisted of 34 questions. The population of this research is 772 students of SMAN 2 Pekanbaru. The sample is 34 students of X IPS 3 class, 34 students of XI IPS 3 class, and 38 students of XII MIPA 1 class. The total is 106 students as the sample. The data of this research were collected by giving questionnaire to the students which then was measured on a Likert scale on scale of 1-5. The results of data analysis showed that the teacher often use English during class and still include Bahasa Indonesia as L1 in a limited portion. The students agree about the inclusion of L1 by teachers when necessary. The students also agree if they are allowed to use Bahasa Indonesia during class. The inclusion of L1 help the students learn more motivated and enjoyable. It was found that there is an improvement in the students’ English skill when English is the language mostly used during class. The students agree that the more they practice using English, the more their English improved.Keywords: Perception, Survey Research, L1